Impacts of X-Ray irradiation on RBC, WBC and PLT by low doses (40kV and 80kV) - Najeba Farhd Salih; Shatha Farhan Alhous; Murtadha Shakir. Aswood; Ansam Fadhel Showard (Journal of the Pakistan Medical Association, 2024)
This study aimed to assess the impact of irradiation on red blood cells (RBCs), white blood cells (WBCs), and platelets (PLTs) using modest doses of X-ray radiation (40 kV and 80 kV). The blood samples were exposed to X-ray irradiation at 40 and 80 kV. A haematology analyzer system with automated capability was used to quantify cellular components, specifically WBCs, RBCs, and PLTs, both before and after exposure to radiation. The study found that irradiation reduced WBC and PLT numbers. When exposed to 40 kV and 80 kV voltages, the WBC and PLT improved statistically significantly (p = 0.001). Nonetheless, the statistical analysis revealed no statistically significant difference (p > 0.05) in red blood cell count between 40 and 80 kV doses. It can be concluded that the haematopoietic system exhibits a high degree of sensitivity to radiation exposure. Keywords: X-Rays, Erythrocytes, Leukocytes, Radiation, Hematopoietic, Haematology